The Comparison of Post Coronary Artery Bypass Graft Functional Capacity between High Intensity Interval Training and Moderate Continuous Intensity Aerobic Exercise in Phase II Cardiac Rehabilitation Patients - Dini Fitriani; Irma Ruslina Defi; Sunaryo B Sastradimaja; Badai B Tiksnadi (Indonesian Journal of Physical Medicine & Rehabilitation, 2020)
ABSTRACT Introduction: Increased aerobic exercise capacity appears to reduce all-cause mortality and cardiovascular mortality. Aerobic exercise improves functional capacity (FC) is strongly recommended.However, evidence regarding the most efficient exercise intensity for patients post Coronary Artery Bypass Surgery (CABG) is still limited. This study aimed to assess the effects of high-intensity intervalexercise (HIIT) compared to moderate-continous intensity exercise (MCT) for increasing FC in patients post CABG. Methods: True experimental pre-post study included 6 men post CABG participating in a phase II cardiac rehabilitation (CR) with age ≤ 65 years old, ejection fraction ≥ 40%, no heart failure, no valve disease.Each group had 3 participants. HIIT group exercise at 80-90% Heart Rate Reserve (HRR) followed by 60-70% HRR active rest periods, MCT group exercised at 60-80% HRR. Both groups trained 3 days/week for 4 weeks. FC measured at baseline and after 4 weeks of rehabilitation. FC was assessed by maximal exercise testing through indirect VO2 max measurement. Results: After training, FC increased significantly in both group HIIT: 0,98±0,48 METs (8.07±1.51 METs to 9.05±1.21 METs), p=0.03 and MCT : 0,79±1,03 METs (5.74±2.24 to 6.53±1.69 METs), p=0.04).Differences in FC improvement between the two groups are p=0.792. Conclusion: HIIT exercise had no difference with MCT in increasing FC in patients post CABG. Keywords: CABG, cardiac rehabilitation, continuous moderate training, functional capacity, highintensity interval training